Improved polypoid Musa germplasm developed through ploidy manipulations - Ortíz, R.; Vuylsteke, D.R. (African Journals Online, 1997)
Plantain and banana (Musa spp. L.) polyploid hybrids have been obtained after interspecific hybridisation and ploidy manipulations (i.e., interploidy crosses). The identification of promising hybrids for cultivar release requires their field testing to assess agronomic performance. The potential of new polyploid hybrid selections was evaluated in comparison with their triploid ancestral landraces in two trials consisting of 25 and 30 genotypes, respectively. Twenty-six primary tetraploids, seven secondary triploids, three secondary tetraploids and one tertiary tetraploid hybrid were evaluated along with seven triploid landraces and three diploid ancestors from 1993 to 1996. Following this extensive on-station field testing and fruit taste panels, seven promising hybrids were selected based on their desirable attributes: desired resistance to biotic stresses, acceptable agronomic traits and adequate fruit quality. The selected hybrids were the black sigatoka-resistant and virus-tolerant primary tetraploids TMPx 7152-2 (plantain), TMPx 7356-1 (plantain), TMBx 5295-1 (starchy banana), and the secondary Musa triploids (TM3x) 14604-35, 15108-1, 15108-2, and 15108-6. This improved germplasm has been advanced for multilocational trials in Nigeria and for local testing in Uganda. After assessing their stability and local adaptation, they may be released as new cultivars in specific agroecozones. The final impact of these Musa hybrids in African agriculture will be measured when this new germplasm becomes an integral component of local farming and food systems.